ASUPAN VITAMIN D YANG KURANG BERISIKO MENINGKATKAN FREKUENSI KEJADIAN ALERGI SECARA UMUM PADA PEREMPUAN DEWASA DI KOTA BOGOR - Pertiwi, Fenti Dewi; Damayanthi, Evy; Rimbawan, Rimbawan (Poltekkes Kemenkes Bandung, 2023)
Vitamin D deficiency is not only caused by disease, but also by insufficient intake. Insufficient vitamin D levels are associated with an increased incidence of allergies. This study aimed to determine the relationship between the source of vitamin D intake and the frequency of allergies in adult women in Bogor City. This research used a cross-sectional design involving 395 women aged 19-49 years and domiciled in Bogor City from August-November 2023. The sampling technique used was purposive sampling based on inclusion criteria. Data collection was carried out by filling out a questionnaire. Bivariate data were analyzed using chi-square. The results of the study show that consumption of vitamin D has a significant effect on the incidence of allergies, where people who consume vitamin D are less at risk of developing allergies (allergic and not allergic) (0.021) and is supported by the statement that the frequency of administration of vitamin D apparently influences the risk of not experiencing allergies ( 0.033). The results showed that intake of other sources of vitamin D: fish (p=0.359), cod liver oil supplements (p=0.106), milk enriched with vitamin D (p=0.844), dairy products enriched with vitamin D (p=0.503) , is not significantly related to the frequency of allergic events. The conclusion is regular consumption of vitamin D supplements can help reduce the frequency of allergies. Further research on the effects of immunomodulation and allergy prevention with experimental approaches is needed. Future research suggestions should investigate the optimal dose of vitamin D supplements for allergy prevention.